Valorization of pineapple peel waste: Investigating cultivation conditions for bacterial cellulose production - Chew, Few Ne; Muhammad Adam Firdaus, Abdullah; Ng, Wei Luo; Rahmatulnisya, Abbas; Chua, Gek Kee (EDP Sciences, 2025)
A fresh pineapple typically produces about 40 to 50% of pineapple peels and cores. If these fruit residues are not properly treated, they can cause severe environmental issues. In fact, pineapple peels are rich in sugar content, which is suitable for use as carbon source in microbial fermentation to produce valuable products like bacterial cellulose (BC). BC is a versatile biomaterial with diverse applications because of its excellent physical and mechanical characteristics. This research aimed to use pineapple peel extract as a substitute for the commercial glucose usually used in the medium. Fermentation uses waste as a substrate for microbial growth and product formation under static conditions, certain growth conditions are necessary to ensure the desired product yield and properties. This study showed that peel juice concentration, the medium pH, the fermentation temperature and the duration significantly influenced both cells and BC concentrations. The best condition for producing BC was recorded when the experiment was set up at a waste juice concentration of 80% (w/v), medium pH 4.0, fermentation temperature of 30°C, and 12 days of fermentation time. This study will enable the efficient utilization of pineapple peel wastes from industry and could help reduce the costs of BC production.